Effects of socio-structural variables in the theory of planned behavior: a mediation model in multiple samples and behaviors. - Hagger, Martin S.; Hamilton, Kyra (Psychology & Health, 2021)
Objective: Observed variation in health behavior may be attributable to socio-structural variables that represent inequality. We tested the hypothesis that variability related to socio-structural variables may be linked to variation in social cognition determinants of health behavior. A proposed model in which effects of socio-structural variables (age, education level, gender, income) on health behavior participation was mediated by social cognition constructs was tested. Design: Model effects were tested in correlational datasets (k = 13) in different health behaviors, populations, and contexts. Samples included self-report measures of age, highest attained education level, gender, and net household income, and constructs from the theory of planned behavior (attitude, subjective norms, perceived behavioral control, intention). Ten samples provided follow-up self-reports of health behavior. Results: Path analyses supported sample-specific indirect effects of gender and age on health behavior with comparatively few income and education level effects. Meta-analytic structural equation modeling indicated consistent indirect and total effects of gender on intentions and health behavior through social cognition constructs, and a total effect of education level on behavior. Conclusion: Results provide support for the proposed mechanism by which socio-structural variables relate to health behavior. Replication in larger samples and meta-analytic synthesis across multiple health behavior studies is warranted.